2015
DOI: 10.5114/wo.2015.51612
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Th17 cell population regulatory cytokines in laryngeal carcinoma – Preliminary study

Abstract: Aim of the studyAim of the study was to evaluate the potential role of regulatory and proinflammatory cytokines IL-23 and IL-17 as Th17 lymphocyte activity markers in relation to invasiveness in laryngeal cancer.Material and methodsThe immunological analysis was conducted in 50 patients treated for squamous cell laryngeal carcinoma and 30 healthy volunteers as controls. The levels of IL-23 and IL-17 in supernatants of purified peripheral blood mononuclear cell cultures were determined by using the enzyme-linke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 32 publications
1
3
0
Order By: Relevance
“…In the present study, serum IL-17 levels did not correlate significantly with the presence of laryngeal SCC, tumour size or nodal involvement. Similar results were reported in a recent study in laryngeal SCC patients, although slightly higher IL-17 concentrations were noted in the control group 36 …”
Section: Discussionsupporting
confidence: 91%
“…In the present study, serum IL-17 levels did not correlate significantly with the presence of laryngeal SCC, tumour size or nodal involvement. Similar results were reported in a recent study in laryngeal SCC patients, although slightly higher IL-17 concentrations were noted in the control group 36 …”
Section: Discussionsupporting
confidence: 91%
“…in laryngeal cancer might inhibit aggressive tumor development, thus contributing to a relatively good prognosis [24]. Kopta R et al found that cytokines IL-23 played critical roles in determining the aggressive potential of laryngeal cancer [25]. The levels of cytokines may be sensitivity and reliable in re ecting tumor microenvironment which hold the capacity to serve as tumor biomarkers.…”
Section: Discussionmentioning
confidence: 99%
“…The IL-17F has the highest degree of homology to IL-17A in the family. T helper cell 17-secreting cells (Th17) are the primary source of IL-17, while other cell types also develop this cytokine, such as group 3 innate lymphoid cells (ILC3), δγ T cells, and natural killer (NK) cells [ 4 6 ]. Some evidence has suggested that IL-17 is a key proinflammatory cytokine for the induction of cytokine and chemokine secretions by other cell types, among which mesenchymal cells and myeloid cells can recruit monocytes and neutrophils for inflammation [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Given the roles of IL-17 in transducing multiple signals in cells, IL-17 also activates Src to promote cancer development [ 6 ]. For example, the PI3K/AKT signaling pathway is one of the major Src-activating pathways and may block the FAS-associated death domain protein to inhibit cellular apoptosis [ 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%